A cross-sectional survey of patient's perception and knowledge of dental implants in Japan - Kailing Ho; Shaima Bahammam; Chia-Yu Chen; Yasushi Hojo; David Kim; Hisatomo Kondo; John Da Silva; Shigemi Nagai (SpringerOpen, 2022)
Abstract Background This study aimed to collect data regarding patient perception and knowledge of dental implants. It was conducted with the hope that the data would provide dental professionals and policymakers with a better understanding of ways to promote implant therapy. Methods  An anonymous online survey with 10 questions was distributed through 12 dental offices in Tokyo and provincial cities in Japan to assess patient perception and knowledge of dental implants. Harvard Medical School's IRB approved this study. Results We collected data from 1172 patients (59% female, 41% male). The most common perceptions of implant therapy were that it was "expensive," "advanced," and "scary". Patients' implant knowledge came primarily from magazines or books, while professional dental societies/associations were the least sought out source of information. Patients believed that the purpose of dental implants was to avoid dentures and improve chewing function. Their primary concerns about dental implants were the cost and longevity. Approximately 12% of patients with dental implants and 61% of patients without implants did not know that bone grafts may be required and that sedation during surgery was an option. For patients who experienced sedation during the procedure, 60% of them want it for future surgeries. Patients also had limited knowledge of bone-graft materials and the effects of CBCT radiation; 75% of the patients expressed concerns over the safety of graft materials and radiation exposure. For patients with a history of dental implant therapy, 80% of them would recommend dental implants to their family and friends. Conclusions Overall, patients' experiences with dental implant therapy were positive, but there was a lack of patient education regarding dental implants and their associated procedures. Dental professionals need to take the initiative to improve patient education.